Peningkatan Edukasi bagi Lansia Sehat dan Produktif - Sofiana, Liena; Khusna, Arfiani Nur (Universitas Muhammadiyah Yogyakarta, 2019)
Lack of knowledge of the elderly in maintaining health in facing old age causes many health problems in the elderly. The goal to be achieved in mentoring is that the elderly in the Posyandu Lansia (Integrated Healthcare Center for the Elderly) of the Kauman village of Yogyakarta can improve their health knowledge of the elderly as an effort to live healthily, so as to increase the life expectancy of the healthy and productive elderly people. The end of the mentoring is expected that all elderly participants can find out what is happening to the health of the elderly as an effort to live a healthy life. The material presented in this activity includes knowledge about healthy elderly people, diseases and risk factors that occur in the elderly, as well as nutrition and healthy food for the elderly by using case study methods, consultation for healthy living, and the practice of maintaining physical health. Other activities carried out in increasing knowledge in realizing healthy elderly people are by increasing awareness of the elderly to carry out health checks including blood pressure, blood sugar levels, uric acid, and cholesterol and elderly exercise. The results obtained are knowledge and skills for healthy and productive living procedures for the elderly.